Efforts Of Front Office Department To Increase Guest Satisfaction At Padma Hotel Semarang - Fadia Lutfiana Dahlan; Dedi Joko Purnomo (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Fadia Lutfiana Dahlan C13.2019.00275 Efforts Of Front Office Department To Increase Guest Satisfaction At Padma Hotel Semarang. Hospitality Management Applied Undergreduate Study Program, Faculty of Cultural Sciences, Dian Nuswantoro University. This final project aims to explain the efforts that have been made by the Front Office Department to increase guest satisfaction. There are two obstacles faced by the Front Office Department staff, namely when guests are waiting for long rooms and the problem of AC that is not cold. Basically, guests who visit a hotel with the aim of staying want a comfortable place. Guests who are satisfied with the services provided by staff are important, in this case, the Front Office department is responsible for and has a major influence on hotel guest satisfaction. This research is a research that uses descriptive qualitative research methods. Data collection techniques were obtained through interviews, observation, and documentation so as to obtain accurate data. The research results obtained show that the services provided by the Front Office Department to guests can be assessed as very good in terms of handling complaints to guests, due to handling complaints to guests is one way to satisfy guests. The efforts made by the Front Office Department in increasing guest satisfaction include three things, namely writing guest complaints in the comment log, conducting staff training and following the workflow according to standard operating procedures. With this, efforts can be made to increase the satisfaction of guests staying at Padma Hotel Semarang.